COLORS IN GOND TRIBAL ART: AN INTERPRETATION AND CRITICAL EVALUATION OF COLORS IN GOND PAINTINGS OF MADHYA PRADESH. - Bharadwaj, Kumkum; Ukande, Anu (International Journal of Research -GRANTHAALAYAH, 2014)
Fork-art forms have the great social mission of creating cultural identity. The integrity of individuals and equipping them to meet social challenges are a part of this. In Madhya Pradesh- the heart of India lies the oldest found art heritage in the world. Gond Tribal paintings of Madhya Pradesh have gained worldwide recognition in recent years. The Gond tribe, one of the largest Tribal communities of central India resides in Madhya Pradesh and Chhattisgarh. Over the past decades it has been observed that tribal people are being assimilated with the rest of the population and this process has been a continuous one. With the process of integration arise challenges of retaining, preserving and promoting the cultural elements of the tribes which may face the threat of extinction. This paper attempts to analyze the changes in Gond art brought about by their gradual assimilation into mainstream arts, and the future approaches to colors.